1996
DOI: 10.1093/infdis/173.3.754
|View full text |Cite
|
Sign up to set email alerts
|

Identification by Random Amplification of Polymorphic DNA of a Common Molecular Type of Cryptococcus neoformans var. neoformans in Patients with AIDS or Other Immunosuppressive Conditions

Abstract: Sixty clinical isolates of Cryptococcus neoformans var. neoformans were analyzed by random amplification of polymorphic DNA (RAPD) using 12- to 22-mer primers in pairs. Five major profiles, which clearly distinguished between serotypes A (profiles I-III), AD (profile IV), and D (profile V), were identified. Forty-two of 58 serotype A isolates were assigned to profile I, 13 to profile II, and 3 to profile III. Profile I compromised 5 subtypes (profiles Ia-Ie), with 37 to 42 isolates in profile Ia. Twenty-seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
50
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 14 publications
4
50
0
Order By: Relevance
“…In epidemiological studies of the species a considerable variation of karyotypes, DNA-fingerprints, and RAPDgenotypes has been demonstrated (Polacheck and Lebens 1989;Perfect et al 1993;Dromer et al 1994;Wickes et al 1994;Brandt et al 1995Brandt et al , 1996Varma et al 1995;Chen et al 1996). The genetic make-up of the varieties neoformans and gattii was also found to differ from each other (Wickes et al 1994;Varma et al 1995;Boekhout et al 1997).…”
Section: Introductionmentioning
confidence: 98%
“…In epidemiological studies of the species a considerable variation of karyotypes, DNA-fingerprints, and RAPDgenotypes has been demonstrated (Polacheck and Lebens 1989;Perfect et al 1993;Dromer et al 1994;Wickes et al 1994;Brandt et al 1995Brandt et al , 1996Varma et al 1995;Chen et al 1996). The genetic make-up of the varieties neoformans and gattii was also found to differ from each other (Wickes et al 1994;Varma et al 1995;Boekhout et al 1997).…”
Section: Introductionmentioning
confidence: 98%
“…neoformans, but the two varieties can cause similar neurological syndromes. To diagnose clinical infections and monitor dispersion of strains, technical instruments for cryptococcal genome scanning have been developed (6,8,9,12,29,36,43,44,50,51). Molecular typing techniques have revealed that there is considerable genetic heterogeneity within the species (51,54).…”
mentioning
confidence: 99%
“…Variations in intensity of RAPD-PCR bands were observed, in spite of standardization of DNA concentrations. In this case, the number and reproducibility of the bands were considered independent of the intensity of band (Chen et al 1996).…”
Section: Pfge -mentioning
confidence: 99%
“…The molecular methods contributed for identifying genetic differences among C. neoformans varieties (Currie et al 1994, Barchiesi et al 1995, Chen et al 1996, Klepser & Pfaller 1998, Meyer et al 1999, Calvo et al 2001, García-Bermejo et al 2001, Litvintseva et al 2006, Almeida et al 2007). Some studies suggested that the majority of cases are due to persistence of the original infecting strain, while others suggested that the infections may result from acquisition of new strains.…”
mentioning
confidence: 99%
See 1 more Smart Citation